Repression of linc01555 up-regulates angiomotin-p130 via the microRNA-122-5p/clic1 axis to impact vasculogenic mimicry-mediated chemotherapy resistance in small cell lung cancer - Dan Li; YanWei Shen; Hui Ren; Li Wang; Jin Yang; Yuan Wang (Taylor & Francis, 2022)
Long non-coding ribonucleic acid 01555 (linc01555) is a brand-new long non-coding RNA (lncRNA) that acts a carcinogenic function in various cancers. However, its role in small cell lung cancer (SCLC) is uncertain. This research was to figure out the role of linc01555 in cisplatin (DDP) resistance of SCLC cells and its possible latent mechanism. After establishment of the resistant sub-strain H446/DDP or DMS-53/DDP, detection of linc01555, microRNA (miR)-122-5p and CLICl was done in the H446/DDP or DMS-53/DDP cell line. After intervention, cell biological functions were determined, as well as tube formation ability. The detection of angiomotin (Amot)-p130 and the validation of the regulatory mechanism were performed. Furthermore, tumor xenografts were applied in nude mice to evaluate the effect of linc01555 on DDP resistance in SCLC in vivo. Linc01555 was elevated in SCLC tissues and cells, and in H446/DDP cells or DMS-53/DDP vs. its parental cells; Restraining linc01555 or elevating miR-122-5p repressed the proliferation and metastasis of H446/DDP or DMS-53/DDP cells and vasculogenic mimicry (VM) formation. CLIC1 mediated miR-122-5p to influence the occurrence and development of SCLC. Linc01555 competitively combined with miR-122-5p, which targeted CLIC1. Refrained linc01555 elevated Amot-p130 via the miR-122-5p/CLIC1 axis. Reduced linc01555 refrained tumor growth and DDP resistance in vivo.In short, linc01555 may cause changes in DDP resistance via miR-122-5p/CLIC1 in SCLC. The finding may offer drug targets for SCLC resistance.
Keywords: Biophysics; Biochemistry; Cell Biology; Genetics; Molecular Biology; Pharmacology; Biological Sciences not elsewhere classified; Developmental Biology; Cancer; Hematology; Plant Biology